2018
DOI: 10.17559/tv-20170217110722
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Unconfined Uniaxial Compressive Strength Using Schmidt Hardness and Ultrasonic Pulse Velocity

Abstract: Unconfined Compressive Strength (UCS) of the rocks plays a significant role in geotechnical and rock engineering projects. Due to difficulties UCS estimation is done using indirect methods such as Schmidt Rebound Hammer (RN) and Ultrasonic Pulse Velocity (UPV) tests that are quick and inexpensive tests. This study was performed to provide data consisting of correlations between RN versus UPV and UCS for rock materials. RN and UCS and UPV tests were carried out on 66 rock specimens from 6 different rock samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Therefore, indirect non-destructive tests are frequently employed to obtain empirical equations to estimate the mechanical properties of rocks (Minaeian & Ahangari, 2013). Ultrasonic P-wave velocity (UPV) test for example is one of the essential non-destructive tests, which is employed to investigate some properties of rocks, such as degree of rock weathering (Schmidt, 1951), tensile strength (Hosseini & Shirin, 2015), UCS (Kurtulus et al, 2018), elastic properties (Abdullah et al, 2019), slake durability index (Hosseini, 2016), and the physical properties of rocks (Kurtuluş et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, indirect non-destructive tests are frequently employed to obtain empirical equations to estimate the mechanical properties of rocks (Minaeian & Ahangari, 2013). Ultrasonic P-wave velocity (UPV) test for example is one of the essential non-destructive tests, which is employed to investigate some properties of rocks, such as degree of rock weathering (Schmidt, 1951), tensile strength (Hosseini & Shirin, 2015), UCS (Kurtulus et al, 2018), elastic properties (Abdullah et al, 2019), slake durability index (Hosseini, 2016), and the physical properties of rocks (Kurtuluş et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have proven that nondestructive testing is important in most cases where drilling of the concrete core is not advisable, because of the weakening of concrete structure due to drilling [19]. The drilling process when obtaining concrete core samples from an existing structural member will cause a reduction in the load-bearing capacity of the concrete, thus affecting the integrity of the concrete structure and possibly causing a structural defect in the future [20].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is important to understand that several factors should be in place when evaluating concrete structures using the Schmidt rebound hammer test. Factors such as the surface irregularity of sample, space between impact, surface hardness, age of the concrete sample, moisture of sample, presence of void and calibration of Schmidt rebound hammer [3,13,20,21] are used to evaluate the relationship between nondestructive (Schmidt rebound hammer test) and destructive test on compressive strength of concrete. It was reported that the correlation coefficient showed an excellent relationship between rebound number and compressive strength.…”
Section: Introductionmentioning
confidence: 99%